Research and Experimental Verification of the Dynamic Pose Analysis Method of Advanced Hydraulic Support in a Fully Mechanized Mining Face - Zhang Kun; Ma Kailun; Zhang Zhaoyun; Cui Bin; Xu Yajun; Wei Xuntao; Chen Yong; Zhang Zengbao; Kong Xiangjun; Chen Hongyan; Tian Dan; Yi Ran; et al. (Energy Science & Engineering)
ABSTRACT This study introduces a dynamic pose analysis method for advanced hydraulic supports, driven by the hydraulic cylinder stroke. This method plays a crucial role in the precise control and path planning of the supports. Based on the closed‐loop mechanical structure, the advanced hydraulic support was modeled as a 10‐degree‐of‐freedom robotic arm, driven by the left and right leg cylinders. Given the time‐sharing driving characteristics, the support was analyzed under two distinct scenarios: those driven by the left and right hydraulic cylinders. A forward kinematic model was established using an improved Denavit–Hartenberg (MD‐H) parameter method, and a joint angle‐following model was geometrically constructed. By integrating these models, a comprehensive pose analysis framework was developed, which allows for the derivation of the mapping relationship between cylinder strokes and the overall support pose. To validate the proposed model, simulations were conducted for 20 lifting cases to calculate the motion relationships between cylinder strokes and joint angles, followed by corresponding experimental tests. The experimental results demonstrated that the pose error was less than 1.31% and the position error was below 0.27%. These findings confirm that the model accurately reflects the mapping between hydraulic cylinder strokes and the overall pose of the support. Lastly, a motion relationship equation was derived, linking cylinder strokes to the roof pitch angle. This equation provides an intuitive representation of the mapping between active joints and the overall support pose.